Pengaruh Efektifitas Pembelajaran Jarak Jauh (PJJ) Mata Pelajaran Pai Terhadap Motivasi Belajar Anak Di Cluster Koba Village Purwakarta - Imam Tabroni; Ismayanti; Diaz Budiarti (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
Distance Learning, especially PAI subjects which are carried out online or online. Indirectly this change in learning methods resulted in the effectiveness of learning and learning outcomes. Therefore, researchers observe how important the role of motivation for students in carrying out learning is, with the hope that learning effectiveness can continue to be carried out optimally if learning motivation is also considered good. The results of the instrument validation analysis using the product moment correlation formula with a significance level of 0.05 indicate that the variable x has 30 statement items, 15 valid items and 15 invalid items, while the y variable has 30 statement items with 18 valid items. and 12 valid items. . The value of the reliability coefficient with an rtable of 0.022 obtained a variable x 0.327 and a variable y 0.362. The score of respondents' questionnaire answers was 78 children on the x variable (distance learning effectiveness) of 87.6% and the y variable (Student Learning Motivation) of 85.7%. The results of hypothesis testing were obtained with rcount with a correlation coefficient of -0.082. This value is in the interval 0.00 – 0.199, namely between the x variable (distance learning effectiveness) and the y variable (student learning motivation) with a very low correlation. The percentage of the relationship is 0.007 which means that the variable x (distance learning effectiveness) to the variable y (student learning motivation) is influenced by the variable x by 72.25% and the remaining 27.75% is influenced by other factors outside the variable x. (distance learning effectiveness). far). The value of Fcount = 0.557 while Ftable with df1 = k – 1 (2 – 1 = 1) and df2 = n – 2 = 78 – 2 = 76 with an error rate of 5% then the value of Ftable is 3.978 if fcount > ftable then Ha is accepted and Ho rejected. Meanwhile, if Fcount < Ftable, then Ha is rejected and Ho is accepted. Based on the comparison of the values ​​above, Fcount > Ftable, it can be concluded that Ho is accepted and Ha is rejected, meaning that there is no significant effect between the x variable (distance learning effectiveness) on the y variable (student learning motivation).